Students’ Perceptions of the Directed Listening Strategy in Teaching Listening: a Case Study at a Bible School - Ado, Yuan Maria Agustina; Savitri, Wiwiet Eva (Universitas Pahlawan Tuanku Tambusai, 2026)
Listening comprehension plays an important role in developing students’ overall language proficiency; however, many learners still experience difficulties due to limited exposure to effective listening strategies. In practice, structured listening strategies are not always consistently implemented, particularly in heterogeneous classrooms. This study aims to explore students’ perceptions of the implementation of the Directed Listening Strategy (DLS) in teaching listening comprehension in a Bible School context. A descriptive qualitative case study design was employed, involving classroom observations and semi-structured interviews with students from diverse age groups and educational backgrounds. The findings reveal that students perceived DLS as helpful in supporting their engagement and comprehension during listening activities. The pre-listening stage was considered the most beneficial, as it helped students predict vocabulary, identify main ideas, and reduce confusion. Overall, the study concludes that DLS is a supportive approach for teaching listening comprehension to learners with limited listening experience.